The influence of coach leadership behavior on athletes’ prosocial behavior in sports: The mediating effect of goal orientation and moral disengagement in sports - Xiangui Bu; Zeqi Huang; Shuaiwei Zheng; Yi Zhang; Shasha Ma; Yuliang Kang (PLoS ONE, 2026)
To investigate the impact of coach leadership behavior on athletes’ prosocial behavior in sports, as well as the mediating role of goal orientation and moral disengagement in it, a questionnaire survey was conducted on 1239 athletes. The results showed that democratic leadership behavior has significant positive and negative effects on athletes’ prosocial behavior and antisocial behavior in sports, respectively; Authoritarian leadership behavior has significant negative and positive impact on athletes’ prosocial behavior and anti social behavior in sports, respectively; Both democratic leadership behavior and authoritarian leadership behavior can have a significant indirect impact on prosocial behavior and antisocial behavior in sports through the mediating effect of goal orientation and moral disengagement. Specific mediating paths include independent mediating paths of self-orientation, task orientation, and moral disengagement in sports, and chain mediating paths of self-orientation and moral disengagement in sports. In the future, coaches can enhance democratic leadership, reduce authoritarian leadership behavior, adjust athletes’ goal orientations, and lower moral disengagement levels, thereby suppressing antisocial behavior and promoting prosocial behavior in sports.